Japanese consumers’ valuation of U.S. beef and pork products after the beef trade ban - Peterson, Hikaru H.; Burbidge, Linda D. (My University, 2012)
Analysis of survey data indicates that Japanese consumers discount their willingness to pay for U.S. beef and pork relative to that of domestic products, but that the discounts have declined from 2006 to 2009. The discounts for U.S. products were greater than those imported from other countries in 2006, but the 2009 discounts were statistically indistinguishable across origins. Our findings also suggest than Japan is a receptive market for meat produced with GM-free feed and for meat products meeting full organic standards.
Keywords: Beef; Choice experiment; Country of origin; Japan; Organic; Pork; U.S. exports